International management ethics: a critical, cross-cultural perspective - Jackson, Terence (Cambridge Univ. Press, 2011)
"What can we learn about management ethics from other cultures and societies? In this textbook, cross-cultural management theory is applied and made relevant to management ethics. To help the reader understand different approaches that global businesses can take to operate successfully and ethically, there are chapters focusing on specific countries and regions. As well as giving the wider geographical, political and cultural contexts, the book includes numerous examples in every chapter to help the reader critique universal assumptions of what is ethical. By taking a closer look at the way we view other cultures and their values, the author challenges us to rethink commonly held assumptions and approaches in cross-cultural management, and to apply a more critical approach"--